2011
DOI: 10.1016/j.brainres.2011.09.037
|View full text |Cite
|
Sign up to set email alerts
|

The avian subpallium: New insights into structural and functional subdivisions occupying the lateral subpallial wall and their embryological origins

Abstract: The subpallial region of the avian telencephalon contains neural systems whose functions are critical to the survival of individual vertebrates and their species. The subpallial neural structures can be grouped into five major functional systems, namely the dorsal somatomotor basal ganglia; ventral viscerolimbic basal ganglia; subpallial extended amygdala including the central and medial extended amygdala and bed nuclei of the stria terminalis; basal telencephalic cholinergic and non-cholinergic corticopetal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 351 publications
(832 reference statements)
3
112
0
Order By: Relevance
“…This effect is not due to general memory impairments, as no deficits are observed in tests of nonsocial memory [40]. Because the medial amygdala in birds (formerly nucleus taeniae [43,44]) exhibits at least a modest level of OTA binding [34], the amygdala could be another site of action that by itself, or together with the LS, mediates the effects of OTA observed here.…”
Section: Discussionmentioning
confidence: 88%
“…This effect is not due to general memory impairments, as no deficits are observed in tests of nonsocial memory [40]. Because the medial amygdala in birds (formerly nucleus taeniae [43,44]) exhibits at least a modest level of OTA binding [34], the amygdala could be another site of action that by itself, or together with the LS, mediates the effects of OTA observed here.…”
Section: Discussionmentioning
confidence: 88%
“…A third, but less acknowledged, hypothesis is that the different subdivisions of the anterior DVR as a field are homologous to both cortical and claustrum/amygdala cell types Molnar and Butler, 2002). To address these hypotheses, a number of elegant comparative and manipulation experiments have since been performed, but still with continued conflicting conclusions Medina and Abellan, 2009;Nomura et al, 2009;Uchida et al, 2010;Wang et al, 2010; Aboitiz, 2011;Butler et al, 2011;Kuenzel et al, 2011;Medina et al, 2011;Puelles, 2011;Tanaka et al, 2011;Atoji and Karim 2012;Dugas-Ford et al, 2012;Suzuki et al, 2012).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…We do not yet have an immediate early gene that is activated in pallidal cells to determine if it too forms topographically organized columns with the striatum and pallium. The pallidal cells intermingled in the anterior striatum of birds (Kuenzel et al, 2011) presumably make up the pallidal component of the somatic motor and vocal motor columns. We do not know if there are striatal, pallidal, and arcopallial components to the dorsal pallial columns.…”
Section: Functional Column Organization Of the Avian Cerebrummentioning
confidence: 99%
See 1 more Smart Citation
“…Karten [6,10], Reiner et al [11], Kuenzel et al [12] using various connectional and histochemical methods, demonstrated that only a limited portion of the avian telencephalon shared common properties with the mammalian basal ganglia. This was confined to the basal ventricular ridge (BVR) of the telencephalon.…”
Section: What Are the Boundaries Of The Basal Ganglia In Birds?mentioning
confidence: 99%